73 Heritability of coronary flow reserve. (9th June 2011) - Ahmed, R; Muckett, P; Cook, S
Abstract : Introduction: Coronary flow reserve (CRF) is the ratio of peak coronary flow during maximal coronary artery dilatation to basal coronary flow and is an important predictor of coronary microvascular function. A variety of environmental stimuli have been shown to affect CFR but little is known about the genetic component of CFR. To characterise the genetics of CFR we initially measured in vivo blood pressure (BP) and ex vivo cardiac phenotypes including CFR in two inbred rat strains, Brown Norway (BN) and Spontaneously Hypertensive Rat (SHR) which is a genetic model for hypertension and microvascular dysfunction. We then studied BP and coronary flow (CF) phenotypes in F1 and F2 crosses derived from BN and SHR to estimate the heritability of CFR and its relationship with BP. Methods: Animals were anaesthetized using a mixture of Oxygen and Isoflurane. BP was measured invasively by cannulation of carotid artery. Following BP measurement hearts were excised and rapidly transferred to the ex vivo perfusion apparatus where retrograde perfusion was established using the Langendorff technique. Hearts were perfused with Carbogen buffered Kreb′s solution and paced constantly at 360 bpm. A fluid filled balloon was placed in the left ventricular (LV) cavity to measure the pressure indices. CF, LV developed pressure, myocardial contractility (LV dP/dtmax ) and myocardial relaxation (LV dP/dtmin ) were recorded at baseline, during peak hyperaemia, regional ischaemia (induced by ligation of the proximal left anterior descending artery) and reperfusion. Results: 1) CFR differs significantly between the two inbred parental rat strains. (BN=2.1 ± 0.32, SHR=1.5 ± 0.18, p=2.6×10 −7, n=16 each). 2) Heritability of CFR: Broad sense heritability (the proportion of total phenotypic variance attributable to total genetic variance) for CFR is 62% indicating a large and previously unrecognised genetic component of CFR. 3) Relationship between CFR and BP: We did not find statistically significant correlation between CFR and BP in the F2 intercross (r=0.11, p=0.11, n=176). 4) Relationship between CF and myocardial relaxation (LV dP/dtmin ): LV dP/dtmin correlated strongly with CF during all stages of the experiment (baseline CF, r=−0.36, p<0.0001, reperfusion CF, r=−0.40, p<0.0001). Conclusions: Our results demonstrate that CFR has a significant genetic component and is largely independent of BP effects. Furthermore we demonstrate a very significant relationship between CF and LV dP/dtmin indicating a link between LV diastolic dysfunction and impaired CF. Using 768 SNP genotyping assay for linkage mapping and gene expression analysis with Affymetrix rat gene chip, we will determine the quantitative trait loci and transcripts associated with CFR to improve our understanding of the genomic architecture of CFR.